The client - Grisham, John. (New York : Doubleday, 1993)
Eleven-year-old Mark Sway witnessed the suicide of a New Orleans attorney. Before he died he told Mark a deadly secret about the recent murder of a Louisiana senator whose accused killer, a Mafia thug, is about to go to trial. Mark hires a lawyer, Reggie Love, who loves helping kids overlooked or abused by the system.
Keywords: Legal stories; Mafia -- Fiction; Large type books; Louisiana -- Politics and government -- 1951- -- Fiction